Modelling an Effective Occupational Fraud Prevention Technique in Malaysian SMEs - Nor Hafizah ABDUL RAHMAN; Noradiva HAMZAH; Razana Juhaida JOHARI; Yusarina MAT ISA (Communications of International Proceedings, 2020)
In recent years, various occupational fraud cases involving Malaysian Small and Medium Enterprises (SMEs) have bankrupted the SMEs. Occupational fraud among the SMEs’ employees includes asset misappropriation, corruption, and financial statement fraud. This study aims to model an effective fraud prevention technique for SMEs in Malaysia. Data for this research was collected through a qualitative approach using an interpretive multiple case study. This study used a purposeful sampling technique to select three SMEs in the manufacturing industry as the case studies. The data was analyzed using content analysis in terms of within-case analysis and cross-case analysis. Based on the key findings from this study and the organizational fraud triangle model by Free, Macintosh, and Stein (2007), several items were identified as crucial for the leadership, management control, and culture elements in an effective occupational fraud preventive technique.  The items in the proposed model include, among others, ethical leadership, realistic performance target, code of ethics, sound internal control system, and compliance with policies and procedures. The proposed model would serve as a benchmark to provide guidelines for the SMEs on preventing fraud in their organizations.
Keywords: SMEs; Occupational Fraud; Fraud Prevention.